О модулях над групповыми кольцами нильпотентных групп - Дашкова, О.Ю. (Український математичний журнал, 2012)
Вивчається RG-модуль A такий, що R — кiльце, A/CA(G) не є мiнiмаксним R-модулем, CG(A) = 1, G —
нiльпотентна група. Розглядається система Lnm(G) усiх пiдгруп H ≤ G, для яких фактор-модулi A/CA(H) не
є мiнiмаксними R-модулями. Дослiджується RG-модуль A такий, що Lnm(G) задовольняє або слабку умову
мiнiмальностi, або слабку умову максимальностi як упорядкована множина. Доведено, що нiльпотентна група G,
яка задовольняє цi умови, мiнiмаксна. We study an RG-module A, where R is a ring, A/CA(G) is not a minimax R-module, CG(A) = 1, and G is a nilpotent
group. Let Lnm(G) be the system of all subgroups H ≤ G such that the quotient modules A/CA(H) are not minimax
R-modules. We investigate a RG-module A such that Lnm(G) satisfies either the weak minimal condition or the weak
maximal condition as an ordered set. It is proved that a nilpotent group G that satisfies these conditions is a minimax group.